Plasma processing of nanomaterials - Sankaran, Mohan (Boca Raton : CRC Press, 2012)
"Plasma technology, and its application at the nanoscale, faces new challenges in the synthesis of well-defined nanomaterials, in terms of their size, shape, and composition. With numerous examples of the synthesis of various classes of nanomaterials, this book provides a comprehensive overview of recent developments and advancements in plasma processing of nanomaterials. Combining both experimental and theoretical work, it describes the successful application of plasma processing to synthesize, modify, and process nanomaterials as well as the use of plasma processing in nanoelectronics, catalysis, energy sensors, and nanomedicine. "--
"Preface Green computing is an emerging interdisciplinary research area spanning across the fields of computer science and engineering, electrical engineering, and other engineering disciplines. Green computing or sustainable computing is the study and practice of using computing resources efficiently, which in turn can impact a spectrum of economic, ecological, and social objectives. Such practices include the implementation of energy-efficient central processing unit processors and peripherals as well as reduced resource consumption. During the last several decades and in particular in the last five years, the area has produced a prodigious amount of knowledge that needs to be consolidated in the form of a comprehensive book. Researchers and engineers are now considering energy as a first-class resource and are inventingmeans to manage it along with performance, reliability, and security. Thus, a considerable amount of knowledge has emerged, as is evident by numerous tracks in leading conferences in a wide variety of areas such as mobile and pervasive computing, circuit design, architecture, real-time systems, and software. Active research is going on in power and thermal management at the component, software, and system level, as well as on defining power management standards for servers and devices and operating systems. Heat dissipation control is equally important, forcing circuit designers and processor architects to consider not only performance issues but also factors such as packaging, reliability, dynamic power consumption, and the distribution of heat. Thus, research growth in this area has been explosive"--
Includes bibliographical references and index.
Keywords: Nanostructured materials; Plasma engineering; SCIENCE / Physics; TECHNOLOGY & ENGINEERING / Electronics / Microelectronics; TECHNOLOGY & ENGINEERING / Material Science